Uji Aktivitas Antijamur Ekstrak Propolis dari Lebah Trigona Sp asal Balikpapan terhadap Candida Tropicalis - Muthia Adlina; Indah Woro Utami; Nishia Waya Meray (STIKes Ibnu Sina Ajibarang, 2025)
Fungal infections are common health problems in tropical regions, including Indonesia, because humid environmental conditions support the growth of these microorganisms. Candida tropicalis is the pathogenic fungal species most frequently found, both as the cause of superficial and systemic candidiasis. The increasing resistance to synthetic antifungal drugs, such as fluconazole and ketoconazole, creates the need for alternative therapies that are safer and more effective. Propolis, a resinous substance produced by Trigona bees from various plant sources, is known to contain flavonoids, phenolics, and terpenoids that have important biological activities, including antimicrobial and antifungal effects. This study aimed to evaluate the effectiveness of ethanol extract of propolis from Balikpapan against the growth of Candida tropicalis using the disk diffusion method. Phytochemical screening showed that the propolis extract contained alkaloids, flavonoids, phenolics, tannins, and terpenoids. The antifungal activity test demonstrated that extract concentrations of 80%, 90%, and 100% significantly inhibited fungal growth, with the largest inhibition zone observed at 100% concentration (27.93 mm). Statistical analysis using ANOVA confirmed significant differences among treatments. Therefore, it can be concluded that propolis extract from Trigona bees in Balikpapan has strong potential as a natural antifungal agent. These findings support the utilization of propolis as an alternative natural-based therapy for fungal infections and as a contribution to the development of natural pharmaceutical products.